The evaluation of blast resistance and submergence tolerance of new breeding rice (Oryza sativa L.) lines developed through 4-way marker-assisted breeding - Selvia Dewi Pohan; Noor Liyana Sukiran; Nur Sakinah Mohd Yusri; Shakirah Mohammad Nahar; Jamsari, Jamsari; Noraziyah Abd Aziz Shamsudin (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aimed to create new rice lines with a strong resistance to blast disease and a high tolerance to submergence. This was achieved by introducing Pi and Sub1 QTLs into the popular local rice variety, Pulau Batu using a 4-way marker-assisted breeding technique. The progenies were evaluated both phenotypically and genotypically to identify those that have favorable traits. The 4-way-F3 rice breeding lines that showed exceptional performance were then assessed in both greenhouse and rice field nurseries from April to July 2023, corresponding to the dry season. The blast fungus, Magnaporthe oryzae (MoK19-28) isolated from a local rice field in West Sumatra was utilized as a fungal inoculum to assess the resistance level of established breeding lines against blast disease. Phenotypic blast resistance test was conducted according to the SES-blast-test standard. Consequently, a submergence tolerance test was carried out to assess the tolerance level of breeding lines to submergence over 14 days of vegetative development, following the submergence tolerance test standard. The results indicated that 11 breeding lines exhibited exceptional performance when exposed to blast disease and submergence stress. Blast resistance test showed that 60% of the breeding lines were categorized as resistant, 27% as moderately resistant, and 13% as susceptible. The submergence test indicated that 7% of the breeding lines were categorized as tolerant, 42% as moderately tolerant, 28% as moderately susceptible, and 23% as highly susceptible. Plants with a high survival rate (>70%) tend to have a low elongation percentage rate (<30%) and low changes in chlorophyll content (<30%). In the natural nursery, they exhibited superior performance in comparison to their parental lines, namely Pulau Batu, Inpari 48 Blas, and IR64-Sub1. This study proposed that the selected breeding lines combined Pi and Sub1A QTLs, which enhance phenotypic traits related to blast disease and submergence stress.